Factor related to stunting of children under two years with working mothers in Indonesia - Sri Supadmi; Agung Dwi Laksono; Hastin Dyah Kusumawardani; Hadi Ashar; Afi Nursafingi; Ina Kusrini; Muhamad Arif Musoddaq (Elsevier, 2024)
Objectives: Working women have complex challenges regarding parenting, giving nutrition, and raising children. This research analyses the factors related to stunting in children under two years among working mothers in Indonesia. Methods: We used a cross-sectional design method with a sample size of 2,073 children under two years. The dependent variable is nutritional status, while independent variables consist of residence, maternal age, marital status, maternal education, wealth status, children's age, gender, and early initiation of breastfeeding (EIBF). We analysed the relationship between dependent and independent variables using the binary logistic regression model. Results: Children in urban areas whose mothers work were 1.116 times more likely to experience stunting than those in rural areas (95% CI, 1.107 to 1.124). Married working mothers were 1.500 times more likely than divorced mothers to have stunted children (95% CI, 1.461 to 1.540). Children aged 12-23 months whose mother work were 2.831 times more likely than those aged <12 months to suffer from stunting (95% CI, 2.809 to 2.854). Children under two years who have not received EIBF from working mothers are 1.020 times more likely to experience stunting than those who received EIBF (95% CI, 1.012 to 1.027). Conclusions: Factors significantly related to the stunting of children under two years with working mothers were residence, maternal age, marital status, maternal education, wealth status, children's age, gender, and EIBF. The policy program to reduce stunting in children should focus on scaling up nutrition and action on direct causal factors and underlying causes and various resulting consequences.